Usability Testing of the Automated Self-Administered 24-Hour Dietary Assessment Tool's Respondent Nutrition Report. (29th May 2020) - Lerman, Jennifer; Kaefer, Christine; Subar, Amy; Herrick, Kirsten; Wambogo, Edwina
Abstract: Objectives: Providing nutrition feedback and advice to research participants based on reported dietary intake is feasible, but has not traditionally been undertaken in all settings. However, it is unclear how such feedback is received and understood by participants or the general public absent the guidance of a clinician or professional. We conducted usability testing to assess understanding of a report with personalized nutrition information to respondents who provided dietary data via the National Cancer Institute's Automated Self-Administered 24-hour (ASA24) Dietary Assessment tool. Methods: Two rounds of usability testing (6 participants per round) were conducted in a laboratory equipped with an eye tracker, as well as audio and computer recording. Participants were recruited from the general population and represented a range of race/ethnicities, education levels, and ages. Trained moderators asked participants to freely explore a newly designed Respondent Nutrition Report (RNR) and then guided them through a series of questions designed to elicit information about whether nutrition information was understood and gather feedback on areas of confusion or misunderstanding. In addition to verbal feedback, participant interaction with the RNR was captured via gaze plots and heat maps. Results: Participants requested additional informational text during round 1 of testing, and read text explanations when present in round 2. Participants preferred a narrow vs. wide design such that it would display easily on mobile devices. They focused on numbers enclosed by graphics and lingered on terminology that was unfamiliar or confusing. When large amounts of information were presented in graphs, attention was focused on the first few items presented but then decreased towards the end of rows and the bottom of the page. Highlighted text was not always attended to by participants. Verbal results indicated that choice of words for labels and explanatory text was critical and that participants desired links to more detailed external information when possible. Conclusions: It is possible to design a personalized nutrition feedback report that is well understood by participants. Care should be taken with wording choices, extraneous information should be limited, and testing within the target population is advisable. Funding Sources: None.